Cryptic diversity of the rocky crab genus Glebocarcinus Nations, 1975 (Crustacea: Decapoda: Cancridae): description of a new species from Russian coastal waters of the Sea of Japan based on morphology, DNA and distribution - Marin, Ivan N.; Maiorova, Anastassya S.; Korn, Olga M. (Zootaxa, 2018)
A new cancrid crab species Glebocarcinus kashini sp. nov. (Decapoda: Brachyura: Cancridae) is described from Russian coastal waters of the Sea of Japan. The new species can be clearly separated from relative and sibling, Glebocarcinus amphioetus (Rathbun, 1898), by a less prominent and granulated dorsal surface of the carapace and dorsal surface of the cheliped propodus, less prominent sculpture of the carapace front and bluntly triangular anterolateral teeth of the carapace. Comparison of COI gene sequences supports the subdivision of these two species and shows their clear genetic separation from a related species, the American pygmy rock crab, G. oregonensis (Dana, 1852). Along the mainland coast of the Sea of Japan, G. kashini and G. amphioetus possibly overlap only in Posyet Bay and adjacent areas; the new species is distributed to the north from the bay while G. amphioetus is distributed to the south. Previous and new records of G. amphioetus from the area are discussed.